The place of language in the theoretical tenets, textbooks, and classroom practices in the ESP genre-based approach to teaching writing. (October 2021) - Cheng, An
Abstract: Even with the popularity of genre-based teaching, conceptual blind spots and knowledge gaps still exist regarding the place of language in the ESP genre-based approach to teaching writing. Examining the literature carefully, I explicate in this article how lexico-grammatical features have been attended to in the theoretical tenets, textbooks, and classroom practices in the ESP genre-based approach, an approach that is appealing to writing instructors and ESP practitioners. Regarding theoretical tenets, I unpack the inseparability of lexico-grammatical features from rhetorical organizations or rhetorical contexts in the ESP genre-based approach. With regard to textbooks, I demonstrate the intensive and expert attention to lexico-grammatical features in graduate-level ESP genre-based textbooks. I explore the possibility of using the inductive, guided discovery approach to develop undergraduate-level teaching materials that focus on common, unique, and important lexico-grammatical features. As to classroom practices, I present student-centered discovery-based analysis, detailed explanations, and targeted corpus searches, among other classroom practices that concentrate on lexico-grammatical features in graduate and undergraduate writing classes. I conclude the article by asking whether facilitating students' fluent control of lexico-grammatical features for producing genres should constitute one of the goals of genre-based teaching and, if so, what some of the pedagogical and research practices may be for achieving such a goal. Highlights: Knowledge of the place of linguistic features in genre-based pedagogy is crucial. Lexico-grammatical features are integral to the tenets of ESP genre-based teaching. ESP genre-based textbooks focus intensively on lexico-grammatical features. Various classroom practices concentrate on lexico-grammatical features. Should ESP genre-based teaching aim to develop students' control of language?